2018
DOI: 10.4049/jimmunol.1701666
|View full text |Cite
|
Sign up to set email alerts
|

Human Factor H Domains 6 and 7 Fused to IgG1 Fc Are Immunotherapeutic against Neisseria gonorrhoeae

Abstract: Novel therapeutics against multidrug-resistant Neisseria gonorrhoeae are urgently needed. Gonococcal lipooligosaccharide (LOS) often expresses lacto-N-neotetraose (LNnT), which becomes sialylated in vivo, enhancing factor H (FH) binding and contributing to the organism’s ability to resist killing by complement. We previously showed that FH domains 18–20 (with a D-to-G mutation at position 1119 in domain 19) fused to Fc (FHD1119G/Fc) displayed complement-dependent bactericidal activity in vitro and attenuated g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 56 publications
0
24
0
Order By: Relevance
“…A similar strategy was successfully demonstrated in a recent study showing the effectiveness of a chimeric anti-gonococcal antibody that recognizes LOS epitope and was modified to enhance complement activation through a single amino acid mutation in Fc (37). Besides, previous studies hampering FH recruitment by gonococci using 2 types of FH-IgG chimeric proteins showed resolution of gonococcal colonization in the same mouse model used here (7,38). Thus, both strategies may be useful adjunctives to antimicrobials.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…A similar strategy was successfully demonstrated in a recent study showing the effectiveness of a chimeric anti-gonococcal antibody that recognizes LOS epitope and was modified to enhance complement activation through a single amino acid mutation in Fc (37). Besides, previous studies hampering FH recruitment by gonococci using 2 types of FH-IgG chimeric proteins showed resolution of gonococcal colonization in the same mouse model used here (7,38). Thus, both strategies may be useful adjunctives to antimicrobials.…”
Section: Discussionmentioning
confidence: 77%
“…Serum bactericidal assay. Bactericidal assays with NHS in the presence of C4BP-IgM fusion protein were performed similarly to those described previously (38). Briefly, bacteria were cultured on a chocolate agar plate overnight and subcultured on new plates for at least 5 hours with or without CMP-Neu5Ac, the latter in case of sialylated gonococci.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically the authors noted no enhanced complement deposition in tissues sections taken from the eyes and kidneys of FH6-7/IgG treated and untreated animals, either infected or not with S. pyogenes ( 22 ). Lastly, Shaughnessy et al ( 44 ) also observed no short term renal (increases in creatinine) or hematologic (increases in lactate dehydrogenase or decrease in hematocrit) or adverse side effects following systemic administration of FH6–7/IgG. Although this data is encouraging, future toxicology assessments are required and will take place during the preclinical development of these fusion proteins.…”
Section: Discussionmentioning
confidence: 89%
“…Based on the finding that N. gonorrhoeae also binds FH domains 6 and 7, we have fused these two domains with human IgG1 Fc to create FH SCR6-7/Fc. Ongoing work has shown that FH SCR6-7/Fc is effective against N. gonorrhoeae both in vitro and in vivo (77,78). We speculate that the use of FH SCR18-20/Fc and FH SCR6-7/Fc may provide additive or synergistic activity because these molecules bind to distinct targets on the bacterial membrane.…”
Section: Discussionmentioning
confidence: 89%